2022
DOI: 10.5851/fl.2022.e9
|View full text |Cite
|
Sign up to set email alerts
|

Study on quality-based protocol for meat and meat products

Abstract: In this study, the protocol of quality analysis method of meat and processed meat products was conducted to be used in the development of various products. Meat and processed meat products have many considerations when analyzing the quality compared with other food groups. The determinants of meat quality are pH, meat color, water holding capacity, age, fatty acid composition, marbling, and lipid oxidation. The quality determinants of processed meat products differed from product to product, so whole meat prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…The CIE a* of processed meat products has a major effect on consumer preferences, with high CIE a* favored by consumers ( Lee et al, 2018 ). CIE a* positively correlated with the sensory evaluation scores for color ( Shin et al, 2022 ). Similarly, in our study, the SM group with added ultra-ground SM powder showed lower CIE a* and also scored lower in sensory evaluation compared with these parameters of the control and other USP-treated groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CIE a* of processed meat products has a major effect on consumer preferences, with high CIE a* favored by consumers ( Lee et al, 2018 ). CIE a* positively correlated with the sensory evaluation scores for color ( Shin et al, 2022 ). Similarly, in our study, the SM group with added ultra-ground SM powder showed lower CIE a* and also scored lower in sensory evaluation compared with these parameters of the control and other USP-treated groups.…”
Section: Resultsmentioning
confidence: 99%
“…The CIE a* of processed meat products has a major effect on consumer preferences, with high CIE a* favored by consumers (Lee et al, 2018). CIE a* positively correlated with the sensory evaluation scores for color (Shin et al, 2022).…”
Section: Sensory Evaluationmentioning
confidence: 91%
“…For emulsion stability, 20 g of emulsion was placed in a glass tube divided by wire mesh and heated at 80°C for 30 min. The volumes of water and oil separated from the sample were checked, and the ratio of the separated liquid (v/w) was measured (Shin et al, 2022).…”
Section: Cooking Loss Water Holding Capacity (Whc) and Emulsion Stabi...mentioning
confidence: 99%
“…The textural properties of the cooked emulsions were confirmed by a textural propertymeasuring device (TA-XTplus; Stable Micro System Ltd., England) and a probe with a diameter of 40 mm. The sample was prepared to have a diameter and height of 25 mm, with a measurement speed of 5 mm/s, strain of 50%, and trigger force of 5 g (Shin et al, 2022).…”
Section: Texture Profile Analysismentioning
confidence: 99%
“…Meat and meat products are good protein sources for humans. Meat proteins are wellbalanced in amino acids and contain all the essential amino acids [7,8]. However, older adults often avoid consuming meat products due to difficulties with digestion or chewing.…”
Section: Introductionmentioning
confidence: 99%